Meningkatkan Pemahaman dan Keterlibatan Siswa dalam Ilmu Pengetahuan Bumi dan Antariksa di Sekolah Dasar melalui Pendekatan Pembelajaran yang Inovatif: Sebuah Tinjauan Literatur - Adinda Shafa Shabrina; Zulherman (DIKLINKO JOURNALS PUBLISHER, 2026)
This systematic review examines recent empirical studies (2021–2026) on innovative teaching methods in primary earth and space science, focusing on student conceptual understanding and engagement. Using PRISMA 2020 guidelines, we searched major academic databases (Scopus, Web of Science, ERIC, ScienceDirect, etc.) for peer-reviewed articles. Our thematic synthesis reveals that inquiry-based, project-based, STEM/STEAM, game-based, and digital learning approaches (including augmented/virtual reality) are frequently implemented. For example, STEAM-first instruction was shown to promote deeper conceptual change than STEM-only methods, and AR-based activities consistently enhanced understanding, motivation, and collaboration. Immersive technologies (AR/VR) improve visualization of abstract concepts and boost engagement, often achieving large effect sizes on learning and self-efficacy. Game-based learning also yields moderate-to-large benefits on cognitive and affective outcomes. Teachers’ perceptions and training emerged as crucial: professional development improved educators’ ability to design hands-on STEM tasks and increased student motivation. Reported challenges include teacher content knowledge gaps and resource constraints. Despite positive results, gaps remain in understanding long-term impacts, cross-context generalizability, and the combined effects of multiple innovations. We synthesize practical implications–urging curriculum developers and policymakers to support teacher training, integrate technology (e.g. AR simulations) thoughtfully, and foster environments for inquiry and collaboration. Future research should explore diverse contexts and emerging tools to further enhance earth and space science literacy in primary students.